(untitled) (Contemporary Journal of Social Science Review, 2024)
This research investigates the cultural and linguistic transfer processes in E.M. Forster’s A Passage to India using Vinay and Darbelnet’s translation model. Through a qualitative analysis, the study explores how Indian cultural elements are integrated into the English narrative, examining both direct and oblique translation techniques. Examples such as the use of "pukka sahib" and the depiction of the Marabar Caves demonstrate how cultural nuances are either preserved or adapted for English-speaking readers. The findings highlight the model’s effectiveness in uncovering the complexities of cultural representation in colonial literature, emphasizing the ethical implications and negotiations of cultural identity. This study contributes to translation studies by offering insights into the balance between translation techniques and cultural authenticity, enriching the discourse on postcolonial literary analysis. Future research may expand on comparative translation approaches across various colonial contexts and examine the impact of translated cultural elements on reader reception, deepening our understanding of translation’s socio-cultural influence in literature.